Primož Trubar in internet z vidika inoviranja - Mulej, Matjaž (Stati inu obstati, 2008)
Primož Trubar linked together the following properties: independent thinking, overcoming opposition, establishing his thinking in an enterprising way, skilful avoidance of obstacles, the aim of benefiting users, the vision to create something essential and new, even fundamentally new, capable cooperation with necessary partners, his protest against entrenched practice, which was considered the only correct practice but was not necessarily the only possible practice, his use of new technological and social possibilities to establish his ideas. His introduction of books in Slovene was a long-term, fundamental and genuine innovation showing the author's broad horizon and influence.
Keywords: etika; IKT; inovacije; inovativnost; internet; komuniciranje; kultura; protestantizem; sistemi; teorija sistemov; Trubar, Primož; vrednote